Measuring autonomy support in special needs teachers from a self-determination theory perspective: validation of the Italian version of the learning climate questionnaire - Monacis, Domenico; Sulla, Francesco; Peconio, Guendalina; Limone, Pierpaolo (Frontiers in Psychology, 2023)
Introduction Self-determination construct is a motivation theory used in professional and educational context to foster special needs teachers’ development of metacognition, and psychological wellbeing. The Learning Climate Questionnaire (LCQ) is a validate questionnaire used to underly teachers’ professional and personal competence, and improving social, emotional and career outcomes. The present paper aims to evaluate the degree of reliability (R1) and the adherence of construct validity to the construct of self-determination (R2) of the Italian adaptation of the LCQ. Methods A confirmatory factorial analysis was conducted to evaluate the factorial structure of the LCQ in a sample of Italian special needs teachers (N = 953). Teachers was asked to complete an online version of the LCQ. Construct validity was conducted by relating the learning climate with the basic psychological needs satisfaction, measured with PBNSF, and with academic motivation scale, measured with AMS. Results The analysis showed a good reliability (R1) and construct validity of the Italian adaptation of the questionnaire, with a high internal consistency compared to those obtained in other studies (R2). Discussion Teachers’ autonomy support and teacher-student relation can positively impact the students’ psychological factors and enhance students’ learning motivation and academic achievement. Findings reveal that higher levels of learning climate could also be a key factor in reducing teachers’ negative stress and mental health consequences. Conclusion This study may facilitate further research about the autonomy-supportive learning climate in educational settings in Italy.